(untitled) - Borgen, Robert (Cambridge, Mass., 1986)
Winner of the 1990 American Historical Association's James Henry Breasted Prize. A great book for anyone interested in the Heian period of Japan.
Keywords: Sugawara, Michizane, 845-903,Statesmen; Japan,Biography